Reducing the carbon footprint and environmental emissions of US fast food through the introduction of oil-free technologies - Manko, Yuliia (Global Prosperity, 2025)
Abstract. The article is devoted to the study of the problem of excessive carbon load of the US fast food industry and innovative approaches to its reduction, including the author's methodology for systemic modernization of professional kitchens. The purpose of the article is to substantiate the need to reduce the carbon footprint and environmental emissions in the US fast food sector by optimizing the use of cooking oil and implementing oil-free technologies. During the scientific study, general scientific methods of cognition were used, in particular, analysis, synthesis, induction, deduction, systematization, generalization and modeling. The results of the study show that the US fast food industry is a source of significant environmental load due to the volume of food waste (up to 60 million tons each year), the disposal of 249 million gallons of used cooking oil and excessive energy consumption (up to 4750 kWh/m² per year in kitchen areas). It is shown that effective emission reduction is possible through multi-level measures: the introduction of energy-efficient equipment (fryeres, grills), kitchen electrification, composting, behavioral interventions (menu labeling), which increase the choice of ecological dishes. Particular attention is paid to the initiative of Manko Yu. (Profstore Equipment LLC, Texas), which involves the introduction of oil-free cooking systems (UNOX, VENIX, SIRMAN, Rational, etc.) for small and medium-sized businesses. The planned modernization of 60 kitchens can provide savings of about 360,000 kWh of energy and reduce the use of up to 12,000 gallons of oil per year, which directly affects the reduction of emissions and contributes to the sustainable development of the food environment. The practical significance of the study is to create an effective model for decarbonization of the fast-food sector through innovative modernization of kitchen infrastructure.